Hubungan Tingkat Kegiatan Pasar Tradisional Baru terhadap Perubahan Tata Guna Lahan Perdagangan Jasa di Kota Surakarta - Fimalananda Afriliasari; Rizon Pamardhi Utomo; Galing Yudana (Universitas Sebelas Maret Surakarta, 2017)
Surakarta as a city of culture and commerce services has many economic facilities to develop the trade sector. One of those economic facilities is traditional market. Traditional markets that has just been made by the government to regulate activities of street vendors, hereinafter in this research is referred to as new traditional market. Among four new traditional markets in Surakarta have different activity crowds. Since new traditional markets were established, there was development of trade and services activities around it. In addition, there is also a theory stating that economic activities will cause physical development of city, especially in terms of trade and services land use. So this research has objective to find out how the correlation between levels of activity on new traditional markets in Surakarta with changes in land use around it becomes trade and services functions. This research uses a deductive approach and classified as correlational study. Research analysis technique used is: scoring analysis to assess level of activity on new traditional markets and qualitative relationship matrix analysis to assess correlation between level of activity on new traditional markets with each changes in land use of trade and services sub-variable. The results obtained that level of activity on all new traditional markets in Surakarta has strong correlation to changes in type of trade and services land use around it, has moderate correlation to changes in basic building coefficient, also has strong correlation to changes in floor building coefficient around it. Keywords: land use, new markets, trade and services